The Environmental Ideology in Ancient Lanna Documents - คำยอด สุนทร (Trends of Humanities and Social Sciences Research, 2019)
This article aims to investigate environmental ideology in the ancient Lanna documents, including ancient Lanna laws, beliefs about “inauspicious” issues, Lanna New Year’s books. The concept of ideology by Louis Althusser was employed as a study framework. The findings reveal that the environmental ideology is a dominant conception that the ruling class employed by using both 2 mechanisms: ideology state apparatus (ISA)-the dominant ideological conception, and repressive state apparatus (RSA)-the alternative one. It is focused on reproduction of ideology by means of written records in Buddhist genre. Furthermore, the above-mentioned environmental ideology also establishes the two different attitudes towards the natural environment. First, the ancient law seems righteously focused on the exploitation of nature–taking full advantages of nature. On the contrary, traditional beliefs about “inauspicious” issues and Lanna New Year’s Books express attitude of humility towards nature, because it has its roots in spiritualism, the traditional belief in Lanna society.